Diagnostic performance of miR‐214, BNP, NT‐proBNP and soluble ST2 in acute heart failure. Issue 10 (5th August 2021) - Jin, Yinsheng; Wei, Shuang; Yao, Lingling
Abstract: Purpose: This study aimed to investigate the potential diagnostic value of miR‐214, B‐type natriuretic peptide (BNP), N terminal‐pro BNP (NT‐proBNP) and soluble ST2 (sST2) in acute heart failure (AHF). Method: This study included 176 patients as the AHF group and 60 healthy subjects as the control group from February 2018 to February 2020. Patients in the AHF group were classified according to the New York Heart Association (NYHA) functional classification, including 60 level II patients, 59 level III patients and 57 level IV patients. The expression level of miR‐214, BNP, NT‐proBNP and sST2 of both groups were recorded and analysed. Results: The morbidity of cardiovascular diseases was significantly higher in the AHF group than in the control group ( P  < .05). The expression level of miR‐214, BNP, NT‐proBNP and sST2 in the AHF group were all significantly higher than in the control group ( P  < .05). Besides, the expression level of all the molecules in level IV was significantly higher than that of level III and level II, respectively ( P  < .001, P  < .001). In addition, the expression level of all the molecules in level III was significantly higher than that of level II ( P  < .001). The area under the ROC curve of miR‐214, BNP, NT‐proBNP and sST2 were 0.913, 0.836, 0.849 and 0.855, respectively, indicating good diagnostic value. Conclusion: MiR‐214, BNP, NT‐proBNP and sST2 can be used as effective biomarkers for AHF, providing a new strategy for diagnosis and for judging the severity of AHF.